LEADERSHIP STYLES IN FAMIILY BUSINESS : AN PT MANDIRI SUKSES UTAMA CASE STUDY - Soegiri, Hary; Hidayat, WandaGemaPrasadio Akbar; -, Suryanto (The International Journal of Accounting and Business Society, 2019)
AbstractThis study aims to provide insight into the meaning and perception of leadership in the family business at PT Mandiri Sukses Utrama. More specifically, this research tries to understand the family business culture context and its importance in developing leadership. We share the view that organizational realities are negotiated and built on the awareness of collective participants. This study uses interpretative case studies. Interviews, observations and documentary analysis are used to collect data. Family business leadership is embedded in the culture of the community. A leader-owner is not the creator but only the manager of organizational culture because he is also a product of the culture of society. Owners and their inner circle (family and not family members) can collectively play an important role in producing and reproducing legitimate MCS based on the extended family concept. In this case, cultural controls based on shared family norms are the most dominant and simplify process and outcome controls. However, business pragmatism can go hand in hand with culture in providing space for MCS transformation. The family business studied is still run by the first generation of families, does not have a subsidiary. The sample size of this study is limited. This study encourages family business owners to consider the use of strong cultural controls along with bureaucratic control to create sustainable organizations.Keywords: Leadrship Style, Management Control System